Defect-selective dry etching for quick and easy probing of hexagonal boron nitride domains. (9th February 2018) - Wu, Qinke; Lee, Joohyun; Park, Sangwoo; Woo, Hwi Je; Lee, Sungjoo; Song, Young Jae
Abstract: In this study, we demonstrate a new method to selectively etch the point defects or the boundaries of as-grown hexagonal boron nitride (hBN) films and flakes in situ on copper substrates using hydrogen and argon gases. The initial quality of the chemical vapor deposition-grown hBN films and flakes was confirmed by UV–vis absorption spectroscopy, atomic force microscopy, and transmission electron microscopy. Different gas flow ratios of Ar/H2 were then employed to etch the same quality of samples and it was found that etching with hydrogen starts from the point defects and grows epitaxially, which helps in confirming crystalline orientations. However, etching with argon is sensitive to line defects (boundaries) and helps in visualizing the domain size. Finally, based on this defect-selective dry etching technique, it could be visualized that the domains of a polycrystalline hBN monolayer merged together with many parts, even with those that grew from a single nucleation seed.